Perceptions of Assessment: An Interview Study of Participants’ Perceptions of Being Assessed in Swedish Adult Education Colleges - Jönsson, Anders (Frontiers in Education, 2022)
Assessments have been shown to influence students’ learning and motivation. To avoid negative consequences, different strategies have been proposed, such as making a more distinct separation between assessments for summative and formative purposes. In this way, situations are created that are exclusively formative, where students may focus on learning without worrying about test scores or grades. This study has investigated perceptions of such a context, where grading is kept apart from assessment for formative purposes. Semi-structured interviews have been performed with 19 participants at five so called “adult education colleges”. At these colleges, students’ “grades” are determined as a joint decision by all the teachers together at the end of the academic year, and no grades are communicated to the participants beforehand. Data from the interviews was analyzed with qualitative thematic analysis, identifying four themes relating to participants’ perceptions of assessment. Findings suggest that participants perceive that there is a lack of feedback on overall progress, limiting their possibilities to regulate their learning. Findings also suggest that the participants do not always know when, or on what grounds, they are being summatively assessed, leading to less productive study strategies. The consequences of this particular assessment context thereby seem similar in several respects, as compared to those reported from the ordinary Swedish school system, even though the latter is greatly influenced by numerous summative assessment events.